The Materiality of Ghosts in “The Bench of Desolation” (1910): An Exploration of the Pocket Metaphor - Saito, Sonoko (Litteraria Copernicana, 2017)
The article is an analysis of Henry James’s “The Bench of Desolation” (1910) from the perspective of the pocket metaphor. The author focuses on one text, referring to interpretations by other scholars, such as Millicent Bell and Martha Banta, and placing the story in a more general context. Saito addresses literary portrayals of men putting hands in their pockets in such works as The Europeans and The Portrait of a Lady. She also discusses the pocket metaphor in The American Scene.